A Scholarship of Practice Revisited: Creating Community-Engaged Occupational Therapy Practitioners, Educators, and Scholars. Issue 4 (2nd October 2015) - Hammel, Joy; Magasi, Susan; Mirza, Mansha Parven; Fischer, Heidi; Preissner, Katharine; Peterson, Elizabeth; Suarez-Balcazar, Yolanda
ABSTRACT: Trends in policy, practice, and research point to the need for a community-engaged Scholarship of Practice (SOP) model that can be used to inform the development of occupational therapy practitioners, educators, and researchers. This article describes a community-engaged SOP model, the evidence justifying the need for such a model, and strategies to effectively create community-engaged practitioners, educators and career scientists within occupational therapy. We highlight several examples of community-based participatory research to further inform this model, and in turn, translate this knowledge back to communities for action and systems change that can affect the lives of people with disabilities and the communities in which they seek to live and participate long term.